Photovoltaic-Integrated Wireless Charging Systems for Electric Vehicles: A Smart City Perspective on Sustainable Urban Mobility - Shikdar, Tareq Anwar; Laaksonen, Hannu (IEEE, 2026)
The rapid growth of electric vehicles (EVs) necessitates charging infrastructures that are efficient, user-friendly, and compatible with renewable energy–driven smart-city ecosystems. Wireless power transfer (WPT) has emerged as a promising alternative to conventional plug-in charging by enabling contactless, automated, and safer energy delivery. In this work, a comprehensive photovoltaic (PV)-integrated wireless charging system (WCS) for EVs is proposed and evaluated through detailed MATLAB/Simulink simulations. The system integrates PV generation with maximum power point tracking (MPPT), battery energy storage supported by bidirectional DC–DC conversion, and a Series–Series (SS) compensated inductive coupling network operating near 85 kHz. Two three-phase configurations are investigated: a static fast-charging system rated at approximately 4 kW for residential single-vehicle applications and a stationary/dynamic charging system delivering approximately 31.5 kW in total for multi-vehicle and public transportation scenarios. Simulation results demonstrate stable operation across all power-conditioning stages, effective energy coordination between PV and battery subsystems, and high wireless transfer performance, with coil-to-coil efficiency reaching approximately 91.7% and overall system efficiencies of about 80% and 90% for the two configurations, respectively. The inclusion of a DC–DC buck converter and an integrated Battery Management System (BMS) ensures smooth voltage and current regulation, safe battery operation, and reliable charging behavior. From a system-level perspective, the proposed PV-integrated WCS can reduce dependence on grid power, alleviate stress on urban distribution networks, and support decentralized, renewable-powered EV charging. The presented framework demonstrates the technical feasibility and practical potential of wireless charging as a key enabler of sustainable and resilient smart-city mobility infrastructures.
Keywords: electric vehicles (EVs); wireless power transfer (WPT); photovoltaic (PV) integration; series–series (SS) compensation topology; dynamic wireless charging; smart cities; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Sähkötekniikka|en=Electrical Engineering|